Implications of median sensory study to the thumb and deltoid/biceps motor unit recruitment on identifying C6 root avulsion in upper neonatal brachial plexus palsy. Issue 1 (27th April 2022) - Hearn, Sandra L.; Pieper, Joel R.; Yang, Lynda J.‐S.; Chang, Kate W.‐C.; Kratz, Anna L.
Abstract: Introduction/Aims: Anatomic representation suggests that a median sensory nerve conduction study recording the thumb (median D1 NCS) may effectively assess upper neonatal brachial plexus palsy (NBPP). We sought to determine the feasibility of technique, establish reference data, and assess its ability to: (a) identify focal upper plexus lesions; and (b) identify C6 root avulsion. In a secondary analysis, we explored the association between absence/presence of motor unit action potentials (MUAPs) during needle electromyography (EMG) of the deltoid and biceps brachii muscles and C6 avulsion status. Methods: A retrospective chart review was performed of surgical patients with severe upper NBPP who ultimately underwent surgical reconstruction (between 2017 and 2020). Median D1 sensory nerve action potential (SNAP) amplitude ranges were determined in affected and contralateral limbs and analyzed by C6 root avulsion status. Also, presence/absence of MUAPs during EMG of the deltoid and biceps brachii was compared between C6 avulsion patients and controls. Results: Thirty‐eight patients were included in our analysis. A median D1 NCS study was readily performed, showing a contralateral limb mean amplitude of 27.42 μV (range, 3.8‐54.7 μV). Most patients had a low ipsilateral median D1 SNAP amplitude, regardless of C6 avulsion status. Detectable MUAPs in either deltoid or biceps brachii on EMG were atypical in C6 root avulsion. Discussion: The median D1 NCS identifies upper NBPP, but does not distinguish C6 avulsions from post‐ganglionic lesions, likely due to the frequent co‐occurrence of post‐ganglionic axonal disruption. The presence of MUAPs on deltoid/biceps brachii EMG suggests C6 avulsion is unlikely. Abstract : See Editorial on pages 3‐5 in this issue .